2022
DOI: 10.3847/psj/ac58fe
|View full text |Cite
|
Sign up to set email alerts
|

The Population of Interstellar Objects Detectable with the LSST and Accessible for In Situ Rendezvous with Various Mission Designs

Abstract: The recently discovered population of interstellar objects presents us with the opportunity to characterize material from extrasolar planetary and stellar systems up close. The forthcoming Vera C. Rubin Observatory Legacy Survey of Space and Time (LSST) will provide an unprecedented increase in sensitivity to these objects compared to the capabilities of currently operational observational facilities. We generate a synthetic population of ‘Oumuamua-like objects drawn from their galactic kinematics and identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 89 publications
(101 reference statements)
0
52
0
Order By: Relevance
“…Previously, Kim et al (2020) estimated that Borisov only lost ∼0.4 m of surface material in the solar system and similarly concluded that compositional observations were not representative of the primordial material. Hoover et al (2022) presented the orbital Figure 10. Schematic diagram showing two distinct stages of an interstellar comet's lifetime.…”
Section: The Relative Importance Of Processing In the Ism And The Sol...mentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, Kim et al (2020) estimated that Borisov only lost ∼0.4 m of surface material in the solar system and similarly concluded that compositional observations were not representative of the primordial material. Hoover et al (2022) presented the orbital Figure 10. Schematic diagram showing two distinct stages of an interstellar comet's lifetime.…”
Section: The Relative Importance Of Processing In the Ism And The Sol...mentioning
confidence: 99%
“…distribution of interstellar objects detected by LSST, assuming that all of the objects had an absolute magnitude similar to that of 'Oumuamua. We show the cumulative distribution functions for b and v ∞ in Figure 12, from Figures 12 and 15 of Hoover et al (2022). The LSST will detect objects out to b ∼ 3 au with 20 km s −1 < v ∞ < 60 km s −1 .…”
Section: The Relative Importance Of Processing In the Ism And The Sol...mentioning
confidence: 99%
See 3 more Smart Citations